Fatty acid-induced mitochondrial uncoupling in adipocytes is not a promising target for treatment of insulin resistance unless adipocyte oxidative capacity is increased. - Frayn, K; Langin, D; Karpe, F (2008)
The release of fatty acids from white adipose tissue is regulated at several levels. We have examined the suggestion that fatty acid release might be diminished by upregulation of mitochondrial fatty acid oxidation in the adipocyte, through increasing mitochondrial uncoupling. The intrinsic oxidative capacity of white adipose tissue is low, and older studies suggest that there is little fatty acid oxidation in white adipocytes, human or rodent. We have examined data on fatty acid metabolism and O(2) consumption in human white adipose tissue in vivo, and conclude that increasing fatty acid oxidation within the oxidative capacity of the tissue would produce only small changes (a few percent) in fatty acid release. The major locus of control of fatty acid release beyond the stimulation of lipolysis is the pathway of fatty acid esterification, already probably targeted by the thiazolidinedione insulin-sensitising agents. An alternative approach would be to upregulate the mitochondrial capacity of the adipocyte. We review proof-of-concept studies in which the phenotype of the white adipocyte has been changed to resemble that of the brown adipocyte by expression of peroxisome proliferator-activated receptor coactivator-1alpha. This increases oxidative capacity and also leads to fatty acid retention through upregulation of glycerol-3-phosphate production, and hence increased fatty acid re-esterification. We conclude that prevention or treatment of insulin resistance through alteration of adipocyte fatty acid handling will require more than a simple alteration of the activity of mitochondrial beta-oxidation within normal limits.